Mengintegrasikan ESD ke dalam kurikulum sekolah menengah: Strategi dan model implementasi - Syahrul Bachtiar; Dwi Ajni Shafarwati (Curricula: Journal of Curriculum Development, 2026)
Education for Sustainable Development (ESD) is crucial for fostering students' capacity to address sustainability challenges. Despite its growing application, comprehensive insights into pedagogical strategies are limited. This study conducted a systematic literature review (SLR) in accordance with PRISMA 2020 guidelines, analyzing 29 empirical articles indexed in Scopus, Web of Science, and ERIC. Thematic analysis revealed four key findings: 1) A holistic sustainability competency framework serves as the dominant theoretical foundation; 2) Key pedagogical strategies include project-based learning, STEM-ESD, and inquiry-based learning; 3) Subject-based approaches dominate implementation models, although interdisciplinary and whole-school approaches are gaining ground; and 4) Teacher professional development is a key enabler, while competency gaps and a crowded curriculum are key barriers. Research confirms the positive impact of ESD on sustainability knowledge, attitudes, and critical thinking. These findings suggest that effective ESD integration requires aligning pedagogical innovation with institutional support, ongoing teacher development, and a coherent school culture.